An in vivo membrane fusion assay implicates SpoIIIE in the final stages of engulfment during Bacillus subtilis sporulation - Sharp, Marc D. (The National Academy of Sciences, 1999)
Shortly after the synthesis of the two cells required for sporulation in Bacillus subtilis, the membranes of the larger mother cell begin to migrate around and engulf the smaller forespore cell. At the completion of this process the leading edges of the migrating membrane meet and fuse, releasing the forespore into the mother cell cytoplasm. We developed a fluorescent membrane stain-based assay for this membrane fusion event, and we isolated mutants defective in the final stages of engulfment or membrane fusion. All had defects in spoIIIE, which is required for translocation of the forespore chromosome across the polar septum. We isolated one spoIIIE mutant severely defective in chromosome translocation, but not in membrane fusion; this mutation disrupts the ATP/GTP-binding site of SpoIIIE, suggesting that ATP binding and hydrolysis are required for DNA translocation but not for the late engulfment function of SpoIIIE. We also correlated relocalization of SpoIIIE-green fluorescent protein from the sporulation septum to the forespore pole with the completion of membrane fusion and engulfment. We suggest that SpoIIIE is required for the final steps of engulfment and that it may regulate or catalyze membrane fusion events.